Studying the Exemplification of the Consumption of the Majority of Properties in Charities for the Adventitious Prodigality with a Look to Imamayeh Fiqh - Hussain Yousefifar; Hussein Ahmari; Ali Vaez Tabasi (آموزه‌‌های فقه مدني, 2021)
The consumption of all or majority of properties in charities by some people is of the issues that there are different opinions about inserting it to the adventitious prodigality for being unusual act. Some Islamic jurists with adducing to the absoluteness of the holy Quran verses and many Islamic traditions which they have ordered to donate do not believe that it is an act of a prodigal (Arabic: سفیه safih) and some other jurists with adducing to the Quran verses and Islamic traditions which absolutely forbid extravagance even in charities think that it is extravagance and wastefulness and believe the prodigality of its performer (agent; doer). Some others for combining these two theories guide the discussion to the almsgiver (donor) and believe that the criterion for knowing the rightness (truthfulness) and untruthfulness of prodigality for this act is the amount of his knowledge and trust in God. In the circumstance of the absence of this feature his act is prodigal. Meanwhile presenting a comprehensive explanation of each theory this research has examined and studied the evidences of these opinions and finally with accepting the role of custom in this issue and studying the different aspects of this act and counting some of these states a prodigal act and some others not being prodigal, it can be said that if there is not the factor of the repetition the indication (revealer) of this act cannot denote the prodigality of almsgiver.